Na teia do discurso : os acordos ortográficos e implicações na política linguística de promoção e difusão do Português Língua Estrangeira (PLE) - Conceição, Jailson Almeida (2011)
This research is situated at the interface of Language Policy in Critical Discourse Analysis and its theme is the New Orthographic Agreement as a discursive practice of orthographic unification for a language policy aimed at spreading the Lusophone countries where Portuguese is a foreign language (PFL). The history of orthographic agreements between Brazil and Portugal justifies itself the existence of varieties of the Portuguese language. The Brazilian Portuguese (BP) and European Portuguese (EP) conceived as varieties of the Lusophone system have different achievements within the morphosyntactic, phonological, semantic and pragmatic plans and also in terms of spelling. These differences are not reducible to pure language dimension, since it is understood the language as a form of socialhistorical, ideological, and cultural action and interaction, whose social practices are, at the same time, products and processes of social representations of historical and ideologically oriented groups. From this perspective, it is tried to understand the ways of ideological reproduction of power groups, which constituted the pivot of the successful and failure narrative history around the orthographic agreements between these two countries and in what extent the control of these groups reproduce a colonialist view in the current configuration of the New Orthographic Agreement as a language policy of Lusophony diffusion, currently represented by the nations that comprise the Community of the Portuguese Language Countries (CPLC). So, it is the New Orthographic Agreement as a communicative event in this contemporary, and , by itself, it is tried to reconstruct the past hapenings about the other agreements to better understanding the reproduction of colonialist ideology and the construction of discursive practices that indicate the existence of a Against-Power, guided by an anti-colonialist. The background texts that serve as an anchor for the reconstruction of discursive meanings refer to two interviews, given to the newspaper named Folha Dirigida, in 2010, by the following interviewed people: Evanildo Bechara and Ernani Pimentel, whose opinions regarding the New Orthographic Agreement are divergent. In a last analysis, it is tried to design the sedimented meanings in these speeches to evaluate in which extent the agreements have contributed to the strengthening of a policy of promotion and dissemination of Portuguese as a Foreign Language.